PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PT SUNSON TEXTILE MANUFACTURER - NUNUNG, AI (Politeknik Dharma Patria Kebumen, 2018)
This research is knowing effect on employee productivity monitoring the production of PT Sunson Textile Manufacturer, Supervision as an independent variable (x) and labor productivity as the dependent variable (y), and this study takes the number of respondents as many as 48 people. Data obtained through the questionnaire and then further processed to be tested through statistical analysis such as a simple regression nalysis, t-test and correlation analysis and determination with the help of using SPSP version 17. Result show than the results of t-test of hypothesis testing. (5,757 ) (2,013 ). This ni indicates that moitoring signifikan effect on the level of employee productivity. The amount of supervision on employee productivity in the production of PT Sunson textile manufacturer PT sunson Textile manufacturer Thorn is at 41,9 %.